Protecting the Environment with Criminal Law - Ragnheiður Bragadóttir (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract As concern about the environment has risen during the last few years, international organisations and conventions have encouraged nations to use punishment for environmental offences as one means to fight for a better environment. Icelandic law contains various types of penal provisions in statute laws designed to protect the  environment. However, no comprehensive legislation on matters of environmental impact or provisions on punishment have been enacted. Instead, various existing laws were revised and modernised so as to incorporate environmental protection - often to fulfil international requirements. The Penal Code from 1940 contains provisions which were not enacted in reference to offences against the environment, but might nonetheless be applicable in this regard. In 1999 a new provision on serious offences against the environment was enacted in the Penal Code. Many of these aforementioned statute laws on environmental matters include provisions on punishment, i.e., the Act on Nature Conservation; the Act on the Protection, Conservation and Hunting of Wild Birds and Wild Mammals; the Act on Hygiene and Pollution Prevention; and the Act on the Protection against Marine and Beach Pollution. In this paper, these acts and the surprisingly few judgements where they have been at issue are described, as are cases that have been reported and discussed in the media but not been brought before the courts. Finally, there are some reflections on general prevention and why the provisions on environmental offences are rarely applied.